Sustainable Economic Development Through Entrepreneurship: A Study on Attitude, Opportunity Recognition, and Entrepreneurial Intention Among University Students in Malaysia - Wiramihardja, Karina; N’dary, Varha; Al Mamun, Abdullah; Munikrishnan, Uma Thevi; Yang, Qing; Salamah, Anas A.; Hayat, Naeem (Frontiers in Psychology, 2022)
This study explored the effect of attitude towards entrepreneurship, need for achievement, risk-taking propensity, proactive personality, self-efficacy, opportunity recognition competency, entrepreneurship education, uncertainty avoidance, and entrepreneurial knowledge on entrepreneurial intention among the university students in Malaysia. This quantitative study had adopted the cross-sectional design approach and involved 391 university students in Malaysia via online survey. The study outcomes revealed that need for achievement, proactive personality and self-efficacy has a significant positive effect on students’ attitude towards entrepreneurship. Moreover, entrepreneurship education and uncertainty avoidance have a significant effect on opportunity recognition competency. Finally attitude towards entrepreneurship has a positive and significant effect on entrepreneurial intention among the university students in Malaysia. As entrepreneurship offers an alternative career path for people seeking to gain economic prosperity and address social issues, including unemployment, the government should formulate effective policies and regulations that support entrepreneurship activities. Universities and other institutions should play a pivotal role in providing the right exposure via entrepreneurship education while honing the essential traits for a career in entrepreneurship.